Burden of oral precancer and cancer among an indigenous tribal population of South India - An evaluative study - Sivaramakrishnan Muthanandam; Bontha V Babu; Jananni Muthu; Suganya Rajaram; B Sivapatha Sundharam; M Kishore (Wolters Kluwer Medknow Publications, 2022)
Context: Oral cancer is of major concern in the Indian subcontinent and is found to be high among low socioeconomic groups. One such high-risk group is considered to be the tribal people, who are economically and socially marginalised. Aims: The aim of the present study is to assess the prevalence of oral cancer and precancer lesions among the Narikurava population in Puducherry state, India. Methods and Material: A total of 329 Narikurava tribal people were included in this study. Data was collected by clinical examination of the oral cavity by door-to-door screening. The oral cavity was examined for white/red lesions, ulcerative changes, leathery changes and tissue growths. Statistical Analysis Used: Prevalence was calculated in terms of percentages. Descriptive statistics included the calculation of percentages, mean, and standard deviation. Results: The prevalence of precancer in the population is 48.3%. The majority of the lesions were observed in the buccal mucosa: 41.6% had white lesions, 9.1% had red lesions, 0.3% had ulcerations or growth, and 28.3% had leathery changes followed by the labial mucosa: 0.6% had white lesions, 0.6% had red lesions, 0.3% had ulcerations or growth and 16.4% had leathery changes. Conclusions: The present study observed a high prevalence of precancerous lesions among the Narikurava tribe. The main reason for the high prevalence is attributed to tobacco and tobacco-related habits. Hence, cancer control activities should be prioritised. Designing a model to detect precancer and cancer early and to constantly monitor the detected cases in such populations is of utmost importance.